MARTIN LUTHER’S GERMAN TRANSLATION OF THE BIBLE – A POPULAR OR POPULIST APPROACH? (Религиски дијалог и соработка, 2021)
The German Catholic monk Martin Luther (1483−1546),reformer and rebel, who created a schism in the Roman Catholicand Protestant/Evangelical churches, is also well known for histranslation of the Bible from Hebrew (original: Old Testament)and Greek (original: New Testament) into German. In conflict withthe then-head of the Roman Catholic Church, later even causing adispute with the Pope and the Vatican because of its reform topics,he was guided by the premise that the Bible should be understoodpredominantly by the people, and not only by the clergy and theauthorities. Luther’s idea results in a German Bible translation thatdeparts from the sacral Hebrew, Greek, and also Latin (Vulgate)language dogmas moving toward a linguistic interpretation that“looks into the people’s mouths” (“Dem Volke aufs Maul schauen”).This kind of specific rendering leads Luther to break with traditiontwice: firstly by using primarily the original linguistic codes andregisters and secondly by breaking free from the sacramentalfunction of the original Bible text by not translating literally(word-for-word), which was the case with previous German Bibletranslations. The paper highlights the fact that Luther’s rendering ofthe Bible united the Germans linguistically and laid the foundationsfor the so-called German unitary language. In addition, the paperdiscusses whether the popularization of the German language inthe Bible establishes greater proximity to the believers and may beviewed as a popular or even populist instrument.